Comparison of 3% saline and 0.9% normal saline nebulization as diluent in children with bronchiolitis - Shobha Sapkota; Ammara Kaleem; Suffura Huma; Muhammad Aleem Ud-Din; Shabbir Ahmad; Sobia Shah Alam (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the outcome in terms of mean time to disappearance of cough, wheezing, crackles and length of hospital stay in patients treated with sodium chloride 3% with sodium chloride 0.9% as nebulisation diluent in children for suffering from bronchiolitis. Methods: The prospective study was conducted at the Department of Paediatric Medicine Sheikh Zayed Hospital, Lahore, Pakistan, from November 2014 to April 2015, and comprised children aged between 6 weeks and 24 months having bronchiolitis. Group A received 3% sodium chloride and Group B received 0.9% of the same solution. Duration of cough, wheezing, crackles and duration of stay at hospital were compared between the groups. Data was analysed using SPSS 17. Results: Of the 100 patients, there were 50(50%) in Group A with a mean age of 7.17±4.46, and as many in Group B with a mean age of 6.6±3.74. Overall, there were 55(55%) boys and 45(45%) girls. Mean cough and wheezing remission time as well as length of hospital stay was significantly different between the groups (p<0.05). Conclusion: In children having bronchiolitis, 3% saline as nebuliser solution was found to be more effective than 0.9% saline solution. Key Words: 3% saline solution, Bronchiolitis, Wheezing, Crepitations, Hospital stay.